PENERAPAN SIKAP PANDEMI “ PEDULI, AMANAH, NETRAL, DISIPLIN, EFISIEN, MENTAL DAN INOVATIF” DALAM MENINGKATKAN KUALITAS KEDISIPLINAN SISWA DI SEKOLAH/MADRASAH - Nur hayati (Jurnal Teknologi Pendidikan Madrasah, 2020)
To improve the quality of education in schools, not only the role of the teacher but also the role of quality students is also very influential. The teacher has a duty as a teacher, besides that the teacher is also an educator who transfers values ​​as well as a guide who provides direction and guides students in learning. For this reason, teachers must play an active role and place their position as professionals who work with high performance. This study aims to determine how much influence PANDEMI's attitude has in improving the quality of student discipline in schools.